2014
DOI: 10.3109/14767058.2014.955001
|View full text |Cite
|
Sign up to set email alerts
|

Brain stem/brain stem occipital bone ratio and the four-line view in nuchal translucency images of fetuses with open spina bifida

Abstract: Objective: Brain stem depth/brain stem occipital bone distance (BS/BSOB ratio) and the four-line view, in images obtained for nuchal translucency (NT) screening in fetuses with open spina bifida (OSB). Methods: Single center, retrospective study based on the assessment of NT screening images of fetuses with OSB. A ratio between the BS depth and the BSOB distance was calculated (BS/BSOB ratio) and the four-line view observed, and the sensitivity for a BS/BSOB ratio superior/equal to 1, and for the lack of detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…In addition to the absence, 7,8,15,20 or reduced thickness of the IT, 13,14 other potential markers include obliteration of the cisterna magna, 9,10 increased anteroposterior diameter of the brain stem (BS), decreased brain stem to occipital bone diameter (BSOB) and an increased BS to BSOB ratio (BS/BSOB), 11,12,17,18 reduced posterior fossa fluid area 16 and simply an abnormal four-line view. 10,12,18 Other findings linked to early diagnosis of OSB at the nuchal scan, using views other than the mid sagittal view of the face, include small BPD, 21 small BPD to transverse abdominal diameter ratio 22 and reduced cerebral ventricular volume. 23 Initially in 2009, Chaoui et al 7 reported a sensitivity and specificity of 100% for absence of IT for detection of OSB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the absence, 7,8,15,20 or reduced thickness of the IT, 13,14 other potential markers include obliteration of the cisterna magna, 9,10 increased anteroposterior diameter of the brain stem (BS), decreased brain stem to occipital bone diameter (BSOB) and an increased BS to BSOB ratio (BS/BSOB), 11,12,17,18 reduced posterior fossa fluid area 16 and simply an abnormal four-line view. 10,12,18 Other findings linked to early diagnosis of OSB at the nuchal scan, using views other than the mid sagittal view of the face, include small BPD, 21 small BPD to transverse abdominal diameter ratio 22 and reduced cerebral ventricular volume. 23 Initially in 2009, Chaoui et al 7 reported a sensitivity and specificity of 100% for absence of IT for detection of OSB.…”
Section: Discussionmentioning
confidence: 99%
“…5 Over recent years, an abnormal posterior fossa on the mid-sagittal view of the face at the first trimester nuchal translucency scan, performed at 11-13+6 weeks' gestation, has been associated with the presence of OSB. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] The mid-sagittal view of the face has been routinely obtained in order to measure nuchal translucency (NT) thickness and assess the nasal bones as part of screening for chromosomal abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…This observation underlines the feasibility for diagnosing pathological conditions by direct visualization of the affected structure. Using a combined approach of BS-BSOB ratio [13] and single-line sign [14, 15] in addition to our created reference values could improve the detection rate and differential diagnosis of cystic posterior fossa abnormalities such as Dandy Walker malformation, vermian hypoplasia, and BP cyst [13, 16, 17]. …”
Section: Discussionmentioning
confidence: 99%
“…To solve this issue, other posterior brain markers have been proposed . These include measurements of the cisterna magna , the brain stem and the brain stem occipital bone distance (BSOB), the posterior fossa fluid area, and the four‐line view (Figure ) . The anterior–posterior diameter of the cisterna magna can be measured in a mid‐sagittal view .…”
Section: Anomalies Of the Fetal Central Nervous Systemmentioning
confidence: 99%
“…66 These include measurements of the cisterna magna, the brain stem and the brain stem occipital bone distance (BSOB), the posterior fossa fluid area, and the four-line view (Figure 3). 67,68 The anterior-posterior diameter of the cisterna magna can be measured in a midsagittal view. 69 Non-visualization of the cisterna magna, or a cisterna magna width below the fifth percentile, achieves sensitivity for OSB of 50% to 73%.…”
Section: Open Spina Bifidamentioning
confidence: 99%